Counseling on Optimizing Child Growth and Development Through Effective Parenting Patterns to Support the Achievement of SDGs 4 (Quality Education) - Garnika, Eneng; Suparjo, Suparjo; Wijayanto, Heri; Widyani, Aprilian; Ardi, Komala Khairani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Children's growth and development is a key factor in determining the quality of human resources in the future. This community service was conducted to determine the parenting patterns of parents in Sepakek Village, the factors that influence them and their impact on children's growth and development. Parenting styles, such as authoritarian, permissive, or democratic, have a significant impact on children's physical, emotional, social, and cognitive development. This study also highlights the role of education, economic status, cultural values and access to information as main factors influencing parenting behavior and aims to support Sustainable Development Goals (SDGs) 4 in Sepakek Village. Interventions in the form of counseling and advice have been proven to increase parents' understanding and skills in parenting effectively and have a positive impact on children's development. The findings of this community service will be a reference for improving the quality of child care in Sepake Village through educational programs and government support.